Social Innovation in Faith-Based Organizations: The Role of Nahdlatul Ulama in Preventing Early Adultery and Sexual Violence Among Indonesian Youth - Mochammad Najmul Afad; Maghfur Ahmad; Nur Fajariyah; Siti Mumun Muniroh; Abdul Basid (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Family issues are at the heart of challenges like early marriage and sexual violence. Historically, these problems have been regarded as private matters, making them difficult to address. As the smallest unit of society, the family plays a vital role in tackling these issues. Nahdlatul Ulama, the largest mass organization in Indonesia, has pioneered an important approach by emphasizing the family as a key solution to these challenges. This article explains social innovation in preventing early marriage and sexual violence among young people with a study of the Gerakan Keluarga Maslahah Nahdlatul Ulama (GKMNU) movement. This research uses an qualitative approach with participatory observation and in-depth interviews taking locations in three regions, including Pekalongan Regency, Pekalongan City and Batang Regency. This research analyzes social movement theory and incorporates social innovation concepts. The results of this research show that the GKMNU has implemented several empowerment programs for the community including (1) Maṣlaḥah and Ma’rūf Relations, Good Parenting; (2) Healthy Family (3) Prosperous Family which contains messages of increased income, assets, resilience and (4) Educated Family. The GKMNU program runs using a cultural and structural approach in building a movement that has been proven to have a significant impact on society. The results of this research recommend that GKMNU become a movement that continues to be carried out by continuing to involve all elements and stakeholders of society and continuing to innovate.